Metabolic Engineering of Microbial Cell Factories for the Sustainable Production of High-Value Compounds - Li, Jinyu (Scientific Journal of Technology, 2026)
Microbial cell factories represent a cornerstone technology for sustainable biomanufacturing, offering environmentally friendly alternatives to traditional petrochemical synthesis. This review examines recent advances in metabolic engineering strategies employed to optimize microbial production platforms for high-value compounds, including pharmaceuticals, nutraceuticals, biofuels, and specialty chemicals. We systematically analyze the integration of systems biology approaches, synthetic biology tools, and computational methods that have revolutionized strain development. Our comprehensive analysis of current methodologies reveals that combinatorial engineering strategies, coupled with machine learning-guided optimization, achieve yield improvements of 50-300% compared to conventional approaches. The results demonstrate that engineered Escherichia coli, Saccharomyces cerevisiae, and Corynebacterium glutamicum strains can achieve industrially relevant titers exceeding 100 g/L for various metabolites. We discuss the critical bottlenecks limiting commercialization, including genetic stability, metabolic burden, and scale-up challenges. Future perspectives highlight emerging technologies such as cell-free systems, microbial consortia, and continuous evolution platforms that promise to further accelerate the development of next-generation bioproduction systems.